STUDENT-BASED ASSESSMENT VS. TEACHER ASSESSMENT: IS THERE ANY CONSISTENCY? - Setiawan Adi Prasetyo; Aninda Nidhommil Hima (IAIN Syekh Nurjati Cirebon, 2019)
In Second Language Writing class, the use of student-based assessment such as self and peer assessments has been increasingly promoted in addition to the teacher-assessment (Alias, Masek, & Salleh, 2015; Chang, Tseng, & Lou, 2012; Esfandiari & Myford, 2013) to help the students make a good writing product (Andrade, Du, & Mycek, 2010). Nevertheless, the inclusion of the student-based assessment result in determining the studentsâ€™ final score still becomes a controversial matter since some studies prove that the student-based assessment and teacher assessment are not in agreement and tend to be questionable (Alias et al., 2015; Panadero, Romero, & Strijbos, 2013). Therefore, to bridge the gap, this study aims at investigating the level of consistency among self-assessment, peer assessment, and teacher assessment in a writing course. Through a correlational research design, the current study involved 21 students who took a paragraph writing course and experienced in self and peer assessing. Â To collect the data, the students were asked to write an expository paragraph that was assessed through self, peer and teacher assessments.Â After collecting the data, then the data analysis is done by using Spearman Rank Order Correlation to answer whether or not there is consistency among self-assessment, peer assessment, and instructor assessment. The results reveal that the students provided the same score in self, peer and teacher assessment. However, the correlations in both self and peer-assessment, as well as self and teacher assessment, are not considered statistically significant. The significant difference occurs in the correlation between peer and teacher assessment result only. From this finding, it can be recommended to the teacher to include the result of peer assessment in determining the students' final grade.